Physical Spaces for Virtual Realities: Forging Legitimacy of Immersive Social Documentaries - Boato, Anja (Mimesis Journal, 2024)
The emerging interest in Extended Realities within the digital-arts realm is predominantly driven by their integration into festivals and museums as arenas of cultural legitimization. This article aims to delve into the significance of VR social documentaries within these cultural-validation spaces and to comprehend the distribution channels of such works along with their potential impact on social perceptions. I will delineate the landscape of VR documentaries showcased at festivals from 2021 to 2023, with a particular focus on five of the world’s largest Extended Reality events. Subsequently, I will explore how immersive social documentaries might shape the aesthetic paradigms that have been prevalent in festivals. Finally, I will examine two case studies from a distribution standpoint: The Key (Tricart 2019) and All Unsaved Progress Will Be Lost (Courtinat 2022).